1956
DOI: 10.1111/j.1151-2916.1956.tb15642.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Viscosity, Nuclei Formation, and Crystal Growth in Titania‐Opacified Enamel

Abstract: This investigation shows that there is a relationship between viscosity, number of nuclei, and crystal growth during the firing of titania‐opacified enamels. This agrees with a similar relationship which Tammann found in his experiments with organic glasses. The history of the development of the size, shape, and relative number of particles per unit area of titanium dioxide crystals was traced from 650° to 1300°C. As the temperature increased from 700° to 1100°C., the color of the specimens viewed under reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Beginning at 35 min milling time (D 50 w 3 mm) the fired samples had presented an increase in the contact angle between the glaze and the tile surface, probably due to a greater interaction of the melted glaze with air during heat treatment [3,6,[15][16][17]25]. This is the reason why the contact angle increased with longer milling times (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Beginning at 35 min milling time (D 50 w 3 mm) the fired samples had presented an increase in the contact angle between the glaze and the tile surface, probably due to a greater interaction of the melted glaze with air during heat treatment [3,6,[15][16][17]25]. This is the reason why the contact angle increased with longer milling times (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During firing if the surface tension between the glaze and the tile surface increases (due to the extreme particle size reduction and glaze composition) a strong interaction between the glaze and air occurs, resulting in air encapsulation by the glaze [3,6,[15][16][17]25]. The glaze coat is filled with air bubbles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…present in the raw materials produced nonwhite coats until more pure forms of TiO 2 became available [2]. Some studies reported the relationship between TiO 2 crystallite size and shape and the resulting reflectance and color, identifying rutile and anatase phases, with the acicular rutile particles occurring at higher temperatures or longer firing times and the rounded anatase particles forming earlier in the firing process [3]. Blue color was associated with the smaller rounded anatase particles and yellow color, formed at the later stages of firing, was associated with the dissolution of the anatase particles at the expense of the larger rutile particles.…”
Section: Introductionmentioning
confidence: 99%